Amiloidosis Secundaria o Sistemática: Diagnóstico por la Biopsia Oral y por Patología Clínica en Relación con Pacientes Portadores de Enfermedades Crónicas en Especial TBC Crónica - Gutierrez Manay, Juan J. (2003)
The present investigation incluided: 100 samples, 20 control groups (Universidad Nacional Agraria students), and 80 patients infected with HIVIAIDS; 25 with level If, 35 with level III, and 20patients with level IV. Average proteinic fractions and salivary percentage were taken: Albumin 45.15%, SALIVARY ALBUMIN 15.2%, GAMMAGLOBULIN 75.94% (SIGNIFICANCE LEVEL 1.00%). Problem Sample.- In the problem sample we can see a considerable alteration in the serical electrophorelics proteins. Spit: level II, 22.12% albumin, gammaglobulin 77.64%, level III, albumin 16.35%, gammaglobulin 83.49%. IV 7.71% albumin and 92.37% gammaglobulim. There is a diferrential relationship between normal values of serical gammaglobulim and salivary ones, in HIV/AIDS infected patiens and there is an increase of bucal pathologies.